A Design and Evaluation of a SNEDDS-Based System for Temu Ireng (Curcuma aeruginosa Roxb.) Extract: Enhancing Antioxidant Efficacy Using the SLD Technique - Urmatul Waznah; Riska Kurnia Oktaviani Oktaviani; Shabrina Ainin; M. Iskandar Khafid; Eko Mugiyanto (Universitas Ahmad Dahlan, 2025)
Temu Ireng (Curcuma aeruginosa Roxb.) is known for its strong antioxidant properties, primarily due to its bioactive compounds such as curcumin. However, these chemicals' lipophilia and instability in traditional formulations frequently limit their bioavailability. To address these challenges, a Self-Nanoemulsifying Drug Delivery System (SNEDDS) was developed using the Simple Lattice Design (SLD) method to improve the chemical and physical properties of Temu Ireng extract by forming a stable nanoemulsion that is uniformly distributed in the digestive system. This study aimed to formulate and evaluate a SNEDDS of Temu Ireng extract using the SLD approach, with a focus on enhancing its antioxidant activity. The formulation involved selecting suitable oils, surfactants, and cosurfactants, followed by optimization based on solubility studies, phase diagrams, and thermodynamic stability tests. The SNEDDS was characterized for physical properties such as emulsification time, transmittance, particle size, zeta potential, and polydispersity index. The optimized SNEDDS formulation exhibited excellent characteristics, including an emulsification time of less than 1 minute, near 100% transmittance, a particle size of 9.77 ± 1.33 nm, zeta potential of 0.9 ± 0.1 mV, and a polydispersity index of 0.302 ± 0.033. Antioxidant testing using the DPPH method showed that the 0.1% SNEDDS formulation of Temu Ireng extract had an inhibition concentration (IC50) value of 58.482 mg/L, indicating strong antioxidant activity. The results suggest that the SNEDDS formulation using the SLD method could be an effective strategy to enhance the bioavailability and therapeutic efficacy of Temu Ireng extract as an antioxidant agent.